2021
DOI: 10.1371/journal.pone.0248161
|View full text |Cite
|
Sign up to set email alerts
|

Artificial neural networks for short-term forecasting of cases, deaths, and hospital beds occupancy in the COVID-19 pandemic at the Brazilian Amazon

Abstract: The first case of the novel coronavirus in Brazil was notified on February 26, 2020. After 21 days, the first case was reported in the second largest State of the Brazilian Amazon. The State of Pará presented difficulties in combating the pandemic, ranging from underreporting and a low number of tests to a large territorial distance between cities with installed hospital capacity. Due to these factors, mathematical data-driven short-term forecasting models can be a promising initiative to assist government off… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 40 publications
1
11
0
2
Order By: Relevance
“…The purpose of using the artificial intelligence method was to predict cases, death, mortality, and severity. Since one paper could predict more than one variable, among the 17 papers, seven papers forecasted mortality [1,7,11,[13][14][15]19], five papers forecasted daily report COVID-19 test-positive cases and death cases [4][5][6]12,16], four papers forecasted severity [3,9,17,18], and one paper predicted all of them [20]. Tree-based model was the most common choice, which was used seven times [9,11,12,13,15,16,19].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The purpose of using the artificial intelligence method was to predict cases, death, mortality, and severity. Since one paper could predict more than one variable, among the 17 papers, seven papers forecasted mortality [1,7,11,[13][14][15]19], five papers forecasted daily report COVID-19 test-positive cases and death cases [4][5][6]12,16], four papers forecasted severity [3,9,17,18], and one paper predicted all of them [20]. Tree-based model was the most common choice, which was used seven times [9,11,12,13,15,16,19].…”
Section: Resultsmentioning
confidence: 99%
“…Tree-based model was the most common choice, which was used seven times [9,11,12,13,15,16,19]. The neural network method was a new trend, and five papers applied this method [3,4,5,7,20]. Three papers used the regression method [1,6,17].…”
Section: Resultsmentioning
confidence: 99%
“… Using data around the world and not separating regions or countries by region (??) 17 Wieczorek et al [ 31 ] Forecasting number of cases each day worldwide Information from the last 12 days plus geolocation coordinates of latitude and longitude have an impact on the cases correlations between neighboring countries Proposing a model, which can work as a part of an online system as a real-time predictor to help in the estimation of COVID-19 spread worldwide Using a limited number of data 18 de Barros Braga et al [ 32 ] Estimating the daily and cumulative cases and deaths caused by COVID-19 and demand for hospital beds Cumulative cases Cumulative deaths Municipal demography Occurrence date Name of State's municipalities Names of the health regions Training ANN with data from 6 different moments for providing the ability to evaluate the forecasting quality Using a limited number of data 19 Shetty and Pai [ 33 ] Forecasting the number of infected cases Daily reported cases Applying a fast training algorithm that is Extreme Learning machine to reduce the training time and using cuckoo search (CS) algorithm to select the parameters Not conducting a comparative analysis 20 Tamang et al [ 34 ] Estimating the number of rising cases and deaths in India, the USA, France, and the UK The number of days Presenting intelligent based optimum curve fitting and forecasting for different non-linear models Not conducting a comparative analysis 21 Melin et al [ 35 ] Predicting confirmed and COVID-19 deaths for 26 countries The confirmed and deaths Adopting the firefly algorithm for ensemble neural network optimization to COVID-19 time series prediction with type-2 fuzzy logic in a weighted average integration method Not conducting a comparison with different fuzzy extensions to measure the performance of the adopted model 22 Ardabili et al [ 36 ] ...…”
Section: Related Workmentioning
confidence: 99%
“…The suggested model can be used to perform multistage forecasting for the following days. Braga et al [8] have proposed an approach based on artificial neural networks to predict daily and cumulative cases and deaths caused by COVID-19, as well as forecasting the demand for hospital beds in the Brazilian Amazon. It has been shown that this last model was able to make consistent short-term predictions.…”
Section: Related Workmentioning
confidence: 99%